Analysis of drug efficacy for inflammatory skin on an organ-chip system - Quan, Qianghua; Weng, Ding; Li, Xuan; An, Quan; Yang, Yang; Yu, Bowen; Ma, Yuan; Wang, Jiadao (Frontiers in Bioengineering and Biotechnology, 2022)
Bacterial skin infections cause a variety of common skin diseases that require drugs that are safer than antibiotics and have fewer side effects. However, for evaluating skin disease drugs, human skin tissue in vitro constructed traditionally on Transwell has inefficient screening ability because of its fragile barrier function. With mechanical forces and dynamic flow, the organ-on-a-chip system became an innovative automatic, and modular way to construct pathological models and analyze effective pharmaceutical ingredients in vitro. In this research, we integrated skin extracellular matrix and skin cells into a microfluidic chip to construct a biomimetic ‘Interface-Controlled-Skin-on-Chip’ system (IC-SoC), which constructed a stable air-liquid interface (ALI) and necessary mechanical signals for the development of human skin equivalents. The results demonstrated that in the microfluidic system with a flowing microenvironment and ALI, the skin tissue formed in vitro could differentiate into more mature tissue morphological structure and improve barrier function. Then, following exposing the skin surface on the IC-SoC to the stimulation of Propionibacterium acnes (P.acnes) and SLS (Sodium Lauryl Sulfate), the barrier function decreased, as well as inflammatory factors such as IL-1α, IL-8 and PEG2 increased in the medium channel of the IC-SoC. After this pathological skin model was treated with dexamethasone and Polyphyllin H, the results showed that Polyphyllin H had a significant repair effect on the skin barrier and a significant inhibition effect on the release of inflammation-related cytokines, the effects were more prominent than dexamethasone. This automated microfluidic system delivers an efficient tissue model for toxicological applications and drug evaluation for bacterial-infected damaged skin instead of animals.